Characteristics of Indigenous-owned businesses - Bassirou Gueye; Amélie Lafrance-Cooke; Javier Oyarzun (Economic and Social Reports)
In recent years, Statistics Canada has released data and analysis on business ownership by women and persons with disabilities. Furthermore, in an effort to continue to fill the information gap on business ownership by employment equity groups and better inform policy making, Statistics Canada has released, for the first time, time series on Indigenous-owned businesses by sex of ownership and other characteristics such as age of primary owner and province of operation.